Studi Literatur: Boardgame Peta sebagai Media Joyful Learning pada Mata Pelajaran Matematika Kelas IV SD - Aeni, Devi Nur; Wijayanti, Murwani Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The 21st-century learning emphasizes the development of skills and knowledge that require innovative approaches capable of enhancing students' conceptual understanding and learning interest, especially in mathematics, which is often considered difficult and boring. This study aims to examine the Joyful Learning approach through the use of map-based board games to improve the conceptual understanding and learning interest of fourth-grade elementary school students. The method used is a literature study by collecting data from various relevant written sources, which are then analyzed and synthesized to obtain results. The findings indicate that the map-based board game media can create an enjoyable learning atmosphere and help concretize abstract mathematical concepts. There is an improvement in both students' conceptual understanding and their interest in learning. The conclusion of this study is that Joyful Learning using map-based board games is an innovative and relevant solution to enhance the quality of mathematics learning in elementary schools. Pembelajaran abad ke-21 menekankan pengembangan keterampilan dan pengetahuan yang menuntut pendekatan inovatif yang mampu meningkatkan pemahaman konsep serta minat belajar siswa, khususnya pada mata pelajaran matematika yang dianggap sulit dan membosankan. Penelitian ini bertujuan untuk mengkaji pendekatan Joyful Learning melalui media boardgame peta dalam meningkatkan pemahaman konsep dan minat belajar siswa kelas IV SD. Metode yang digunakan berupa studi literatur dengan pengumpulan data dari berbagai sumber tertulis yang relevan, kemudian dianalisis  dan disintesis sehingga diperoleh hasil. Hasil kajian menunjukkan bahwa media boardgame peta dapat menciptakan suasana belajar yang menyenangkan serta membantu mengkonkretkan konsep matematika yang abstrak. Terdapat peningkatan dalam pemahaman konsep dan dalam minat belajar siswa. Simpulan dari penelitian ini adalah Joyful Learning dengan boardgame peta merupakan solusi pembelajaran inovatif yang relevan untuk meningkatkan kualitas pembelajaran matematika di sekolah dasar.